THE ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) FACTORS AND INVESTMENT DECISION: A CASE OF PAKISTAN - Hilal Ahmad Malik; Dr. Muhammad Salman Qutbi Qureshi; Muhammad Ehsan; Dr. Mohsin Tahir; Yasir Amin; Shoaib Akhtar; Syeda Mahnoor Bukhari (Policy Research Journal, 2024)
This study explores the influence of Environmental, Social, and Governance (ESG) factors on investment decisions in Pakistan, focusing on the evolving role of sustainability in financial markets. Using the Theory of Planned Behavior (TPB) as a conceptual framework, the research investigates how ESG considerations shape the investment preferences of individual investors. Data from 45O individual investors in the Pakistan Stock Exchange (PSX), collected via snowball sampling, was analyzed using STATA. Findings reveal that governance factors have the most significant impact on investment decisions, followed by social and environmental factors. Investors are highly responsive to ESG considerations, with their perceptions playing a critical role in shaping investment outcomes. The study emphasizes the need for businesses to enhance their ESG performance to attract investment and addresses a critical research gap by examining individual investor perspectives on ESG integration. These insights offer practical implications for policymakers, financial institutions, and companies striving to foster sustainable investment practices in Pakistan.